Successful Treatment of a Coxofemoral Luxation in a Shetland Pony by Closed Reduction and Prolonged Immobilization Using a Full-Body Animal Rescue Sling - Miriam Sprick; Christoph Koch (Case Reports in Veterinary Medicine)
A 12-year-old, 170 kg, Shetland pony mare was presented with an acute severe right pelvic limb lameness and concurrent upward fixation of the right patella. The affected limb was rotated externally and adducted with a prominent greater trochanter and the right calcaneal tuber being more proximal than its left counterpart. Radiographic examination revealed complete dislocation of the right femoral head from the acetabular cavity in a dorsal and caudal direction. A closed reduction of the coxofemoral luxation was performed successfully under general anaesthesia. A full-body animal rescue and transportation sling (ARTS) was applied for the recovery. The reduction was followed by a right-sided medial patellar desmotomy. The pony was supported in the ARTS for a total of eight weeks combined with crossties for the first six weeks. Subsequently, the mare was discharged with instructions to slowly increase walking exercise over a period of two months before returning to her intended use. A follow-up after 22 months attested the successful treatment of a coxofemoral luxation by closed reduction and prolonged immobilization resulting in a regularly exercised pony without any residual lameness.